The Relationship of Critical Thinking According to the Five-Factor Model Through Metacognition Mediation: A Path Analysis Model - Mojgan Mohammadimehr (Zanjan University of Medical Sciences and Health Services, 2020)
Background & Objective: The development of critical thinking skills, which is hugely affected by personality traits, was always a puzzling educational subject. This study aimed to elaborate on the relationship of critical thinking according to the Five-Factor Model (FFM) through metacognition mediation among students of the Aja University of Medical Sciences. Materials & Methods: The sample population of this descriptive-correlational study was the 300 students of AJA University of Medical Sciences during the academic year of 2016-2017. A stratified random sampling model used to select the participants. Data was collected by the Traits Personality Questionnaire 5 (TPQue5) developed by Costa & McCrae, Wells' Metacognitions Questionnaire, and Ricketts' Critical Thinking Disposition Questionnaire. Data analyzed with Amos 24 software. Results: According to results there was a significant relationship among four personality traits (p-value=0.001); there was also a positive correlation among metacognition and five personality traits of "openness to new experiences", "conscientiousness", "extraversion", "agreeableness", and "neuroticism" (p-value=0.001). Results indicated a direct and significant relationship between four personality traits and critical thinking (p-value=0.001). However, no direct correlation was observed between agreeableness and critical thinking through metacognition mediation. Conclusion: This study revealed that personality traits could influence the development of critical thinking in medical sciences students.